Beneficial effects of a cognitive-behavioral occupational stress management group training: the mediating role of changing cognitions - Wirtz, Petra H.; Auer, Alisa; Semmer, Norbert K.; Ehlert, Ulrike; Nussbeck, Fridtjof W. (Frontiers in Psychology, 2024)
Introduction: While the effectiveness of cognitive-behavioral stress management trainings (SMT) is well documented, the underlying mechanisms, especially in an occupational context, are not fully understood. We tested whether SMT-induced improvements in stress management skills, in particular in mastery of changing cognitions, may explain beneficial SMT effects. Methods: Our non-randomized controlled trial comprised 108 employees of a German health insurance company with 65 participating in a cognitive-behavioral SMT and 43 participating in an alternative control training (AT). As outcome variables we repeatedly assessed stress-related (functional stress management skills, relaxation, stress reactivity, exhaustion), work-related (job dissatisfaction), and specific-context-related (social support, trait anger) measures at baseline, two weeks, and three months after the trainings. Functional stress management skills and in particular a subscale assessing perceived mastery of changing cognitions (“cognitive-strategies-and-problem-solving”) were tested as mediators of change. Results: Repeated measures (M)AN(C)OVAs and complementary multigroup latent difference models confirmed improvements in all outcomes in the SMT-group compared to the AT-group (p`s≤.015). Multivariate mediation path analyses revealed that regarding mechanisms of change, the subscale cognitive-strategies-and-problem-solving was identified as the most important mediator for all outcomes (95%CIs for expected increases in SMT- vs. AT-group=[lower limits(LLs)≥.004]; 95%CIs for expected decreases in SMT- vs. AT-group=[upper limits(ULs)≤-.078]) except for job dissatisfaction. Discussion: Our findings confirm that employees can effectively learn to master stress reduction techniques and consequently lower resulting burden. Moreover, beneficial SMT effects seem to result from improvements in functional stress management skills, particularly in the ability of changing cognitions. This points to the importance of training cognitive techniques.